Genipin crosslinked soy-whey based bioactive material for atorvastatin loaded nanoparticles: preparation, characterization and in vivo antihyperlipidemic study. Issue 96 (29th September 2016) - Kanoujia, Jovita; Singh, Mahendra; Singh, Pooja; Parashar, Poonam; Tripathi, Chandra Bhusan; Arya, Malti; Saraf, Shubhini A.
Abstract : Lipid lowering potential of soy protein isolate and whey protein concentrate as novel nanomaterial for atorvastatin nanoparticles. Abstract : The aim of the present study was to explore the lipid lowering potential of soy protein isolate (SPI) and whey protein concentrate (WPC) for the development of novel bioactive material as a drug delivery system for encapsulation of atorvastatin (ATR) in nanoparticles (NPs) and to enhance the antihyperlipidemic potential. SPI-WPC crosslinks were synthesized through amine–amine crosslinking reaction using genipin and characterized by FTIR, mass analysis and degree of crosslinking. ATR loaded NPs were prepared by desolvation process and the optimized formulation (ATR/SPI-WPC NPs-10) was selected on the basis of least particle size (158.1 ± 3.8 nm), zeta potential (−33.5 ± 2.6 mV), maximum EE (81.23 ± 1.1%) and DL (31.5 ± 2.9%). X-ray diffractometry spectra confirmed the encapsulation of ATR into NPs, whereas Transmission electron microscopy revealed that NPs were spherical in shape. Additionally, the ATR/SPI-WPC NPs significantly reduced cholesterol level as compare to SPI and WPC, individually. The results of internalization and MTT assay revealed efficient cellular uptake and cytocompatibility of the formulation. The results confirmed that SPI and WPC based bioactive material can be considered as promising biomaterial for encapsulation and enhancement of the therapeutic efficiency of ATR.